PTT / PA eccentric core-sheath composite fiber and preparation method thereof
By introducing alkyl chain modified PA into PTT/PA composite fibers and designing an eccentric core sheath structure, the problem of difficult balance between high strength and high elasticity of composite fibers is solved, and the fracture strength, crimping performance and thermal stability of the fibers are significantly improved, and it is suitable for a variety of high-performance applications.
Patent Information
- Application Number
- CN202510088139.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to achieve a good balance between high strength and high elasticity in existing PTT/PA composite fibers, especially in high temperature environments, the dimensional stability and mechanical properties of the fibers still need to be improved.
By designing a PTT/PA eccentric core sheath composite fiber, alkyl chain modified PA is introduced into the PA sheath layer, and the interface compatibility between PA and PTT is optimized through the design of the eccentric structure, and the fracture strength, curling performance and thermal stability of the fiber are improved.
It realizes the high breaking strength, excellent curling shrinkage and extremely high dimensional stability of composite fibers, and is suitable for a variety of application scenarios that require high strength, high elasticity and high temperature stability.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of fiber technology, and in particular to a PTT / PA eccentric core-sheath composite fiber and a preparation method thereof. Background Art
[0002] Polytrimethylene terephthalate (PTT) has been widely used in the fiber field due to its excellent elastic recovery, wear resistance and dimensional stability. PTT fiber has a low permanent deformation rate and good wrinkle resistance, and is widely used in clothing, home textiles and industrial fields. However, the strength of PTT fiber is relatively low, which limits its application in high-strength demand fields, especially in scenarios that require both high strength and high elasticity. It is difficult for a single PTT fiber to meet the performance requirements. In order to improve the mechanical properties of PTT fiber, it is usually in the form of a composite fiber, and its comprehensive performance is improved by compounding with other high-strength materials.
[0003] Polyamide (PA) is an ideal choice for composite with PTT due to its high strength, high toughness and heat resistance. PA fibers have excellent tensile strength and wear resistance, and also show good dimensional stability in high temperature environments. However, the interface compatibility between PA and PTT is poor, which makes it difficult for the mechanical properties and dimensional stability of the composite fibers to reach ideal levels. The chemical structures of the PA and PTT molecular chains are quite different, and the interface bonding force is weak, which easily leads to interface defects inside the fiber, thus affecting the overall performance of the composite fiber. Therefore, how to improve the interface compatibility between PA and PTT has become a key issue in improving the performance of composite fibers.
[0004] The eccentric core-sheath structure is an effective composite fiber design method. By distributing materials with different properties in the core and sheath layers of the fiber and forming an eccentric distribution, an uneven stress distribution can be generated inside the fiber, thereby giving the fiber excellent curling and elastic recovery properties. The design of the eccentric structure allows the fiber to produce a natural curling morphology during cooling and heat treatment due to the difference in thermal shrinkage between the core and sheath layers, thereby improving the elasticity and recovery properties of the fiber. In addition, the eccentric core-sheath structure can amplify the synergistic effect of the core and sheath materials, allowing the fiber to effectively disperse stress when subjected to force and avoid brittle fracture. However, traditional eccentric core-sheath composite fibers are difficult to achieve a good balance between high strength and high elasticity, especially in high temperature environments, and the dimensional stability and mechanical properties of the fiber still need to be improved. Summary of the invention
[0005] In view of this, the purpose of the present invention is to propose a PTT / PA eccentric core-sheath composite fiber and a preparation method thereof, so as to develop a PTT / PA composite fiber with a significant eccentric core-sheath structure, and to improve the breaking strength, curling performance and thermal stability of the fiber by optimizing the interface compatibility between PA and PTT, so as to meet the requirements of high strength, high elasticity and high temperature stability.
[0006] Based on the above purpose, the present invention provides a PTT / PA eccentric core-sheath composite fiber, comprising a core layer and a sheath layer, wherein the raw material of the core layer comprises PTT chips, and the raw material of the sheath layer comprises PA chips and alkyl chain modified PA.
[0007] Furthermore, the sheath layer accounts for 20%-80% of the total weight of the PTT / PA eccentric core-sheath composite fiber.
[0008] Furthermore, the alkyl chain modified PA accounts for 10%-30% of the total weight of the sheath layer.
[0009] Furthermore, the preparation method of the alkyl chain modified PA is as follows: Step S1: under nitrogen protection, PA slices are crushed through a 50-100 mesh sieve, added to an N,N-dimethylformamide solution containing 20wt%-40wt% formic acid, stirred for 20-40min, potassium permanganate and sulfuric acid are added, stirred for 10-30min, acrylic acid and methyl methacrylate are added, the temperature is raised to 60-70°C, stirred for 1.5-2.5h, washed, and vacuum dried to obtain surface-modified PA; Step S2: adding the surface modified PA to N,N-dimethylformamide, stirring for 20-40 min, then adding stearyl alcohol and p-toluenesulfonic acid, heating to 75-85° C., stirring for reaction for 5-7 h, washing, and vacuum drying to obtain alkyl chain modified PA; Preferably, in step S1, the weight ratio of PA slices, N,N-dimethylformamide solution of formic acid, potassium permanganate, sulfuric acid, acrylic acid and methyl methacrylate is 5-15:50-200:10-30:3-10:1-3:0.5-2.
[0010] Preferably, in step S2, the weight ratio of the surface-modified PA, N,N-dimethylformamide, stearyl alcohol and p-toluenesulfonic acid is 5-15:50-200:5-15:0.5-2.
[0011] Preferably, the PTT slices, PA slices and alkyl chain-modified PA are dried before use, and the water content of the dried PTT slices, PA slices and alkyl chain-modified PA is less than 30 ppm.
[0012] Preferably, the melting point of the PTT slice is 225-230° C., and the relative viscosity is 0.90-1.0; the melting point of the PA slice is 215-265° C., and the relative viscosity is 2.0-3.2.
[0013] Preferably, the PA slice is one of PA6 slice, PA66 slice, PA56 slice, PA11 slice or PA12 slice. Preferably, the eccentricity of the PTT / PA eccentric core-sheath composite fiber is 0.1R-0.3R.
[0014] Furthermore, the present invention provides a method for preparing a PTT / PA eccentric core-sheath composite fiber, comprising the following steps: (1) Drying the PTT slices, PA slices and alkyl chain-modified PA respectively to obtain dry PTT slices, dry PA slices and dry alkyl chain-modified PA; (2) Put the dried PA slices and the dried alkyl chain modified PA from the silo into the twin screw extruder A, and put the dried PTT slices from the silo into the twin screw extruder B. The PA melt melted and homogenized by the twin screw extruder passes through the metering pump A, and the PTT melt passes through the metering pump B, and enters the eccentric core-skin composite spinning assembly for distribution. The melts converge at the spinneret, spin, and then quickly cool and solidify into a filament bundle under side blowing, and finally are formed by oiling and winding to obtain PTT / PA eccentric core-sheath composite filaments. (3) The PTT / PA eccentric core-sheath composite filaments are stretched and heat-set to obtain PTT / PA eccentric core-sheath composite fibers.
[0015] Preferably, in step (2), the temperatures of the four zones of the twin-screw extruder A are 225-275°C, 236-288°C, 240-293°C, and 242-298°C, respectively; the temperatures of the four zones of the twin-screw extruder B are 235-240°C, 246-255°C, 249-260°C, and 255-270°C, respectively; the frequency of the metering pump A is 12-47 Hz; and the frequency of the metering pump B is 11-44 Hz.
[0016] Preferably, in step (2), the specification L / D of the spinneret is 0.9 / 0.4-0.9 / 0.6; the spinning temperature is 270°C; the side blowing temperature is 25-35°C, the wind speed is 0.15-0.25m / s, and the humidity is 70%-80%.
[0017] Preferably, in step (2), the speed of the first godet roller for winding is 550-650 m / min, the speed of the second godet roller is 570-680 m / min, and the winding speed is 600-720 m / min.
[0018] Preferably, in step (3), the drafting ratio is 2.5-3.5 times, and the heat setting temperature is 95-105°C.
[0019] Beneficial effects of the present invention: The PTT / PA eccentric core-sheath composite fiber prepared by the present invention has a significant eccentric structure and exhibits excellent comprehensive performance. When the breaking strength of the composite fiber reaches 3.58 N / dtex, the breaking elongation of the composite fiber is still maintained at 27.4%, and the curling shrinkage rate reaches more than 50%, and it has high strength, high toughness and excellent elastic recovery performance. The design of the eccentric structure enables the fiber to effectively disperse stress when subjected to force to avoid brittle fracture. At the same time, the synergistic effect of the inner and outer layer materials enhances the ductility and fracture resistance of the fiber. In addition, the dry heat shrinkage rate of the fiber at 80°C is less than 2%, showing extremely high dimensional stability. Even at a high temperature of 160°C, the shrinkage rate is still low, showing good thermal stability. It is suitable for clothing and home textiles that maintain their shape in medium and low temperature environments and industrial fibers used in high temperature environments.
[0020] The alkyl chain and methyl methacrylate on the alkyl chain modified PA prepared by the present invention significantly improve the curling shrinkage and breaking strength of the composite fiber, and effectively reduce the dry heat shrinkage. This is because the introduction of the alkyl chain and methyl methacrylate increases the flexibility and mobility of the PA molecular chain, making it easier for the fiber to form a stable eccentric structure, and restricts the thermal movement of the molecular chain, thereby enhancing the interface bonding force and the elastic recovery performance of the fiber.
[0021] In summary, the present invention significantly improves the breaking strength, curl shrinkage rate and dimensional stability of the composite fiber by designing an eccentric structure and introducing alkyl chain-modified PA into the PA sheath layer, and is suitable for a variety of application scenarios requiring high strength, high elasticity and high temperature stability. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0023] In a specific embodiment of the present invention, the melting point of the PTT slice is 225°C, and the relative viscosity is 0.95; the melting point of the PA6 slice is 220°C, and the relative viscosity is 2.8; the melting point of the PA66 slice is 260°C, and the relative viscosity is 3.1; the melting point of the PA56 slice is 265°C, and the relative viscosity is 2.8.
[0024] Embodiment 1:
[0025] (1) Under nitrogen protection, add 5 g of PA6 powder that has passed through a 5-100 mesh sieve into 50 g of N,N-dimethylformamide solution containing 20 wt% formic acid, stir for 20 min, then add 10 g of potassium permanganate and 3 g of sulfuric acid, stir for 10 min, then add 1 g of acrylic acid and 0.5 g of methyl methacrylate, heat to 60 ° C, stir for 1.5 h, then rinse with 10 wt% sodium hydroxide aqueous solution 3 times, rinse with deionized water 3 times, and vacuum dry to obtain surface-modified PA; (2) Add 5 g of surface-modified PA to 50 g of N,N-dimethylformamide, stir for 20 min, then add 5 g of stearyl alcohol and 0.5 g of p-toluenesulfonic acid, heat to 75 °C, stir for 5 h, wash with anhydrous ethanol 3 times, wash with deionized water 3 times, and vacuum dry to obtain alkyl chain-modified PA; (3) drying the PTT slices, PA6 slices and alkyl chain modified PA respectively to obtain dried PTT slices with a water content of 25 ppm, dried PA slices with a water content of 26 ppm and dried alkyl chain modified PA with a water content of 25 ppm; (4) 72 g of dried PA chips and 8 g of dried alkyl chain modified PA were placed from the silo into twin screw extruder A, and 20 g of dried PTT chips were placed from the silo into twin screw extruder B. The temperatures of the four zones of twin screw extruder A were 225°C, 236°C, 240°C, and 242°C, respectively; the temperatures of the four zones of twin screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt after being melted and homogenized in the twin screw extruder was passed through metering pump A with a frequency of 47 Hz, and the PTT melt was passed through metering pump B with a frequency of 25 Hz. The frequency is 11Hz, and the melt is distributed in the eccentric core-skin composite spinning assembly. The melt is combined at the spinneret and spun. The spinneret specification L / D is 0.9 / 0.4, and the spinning temperature is 270°C. Then, the melt is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 25°C, the side blowing speed is 0.15m / s, and the side blowing humidity is 70%. Finally, the melt is formed by oiling and winding. The speed of the first guide roller is 550m / min, the speed of the second guide roller is 570m / min, and the winding speed is 600m / min, thereby obtaining a PTT / PA eccentric core-sheath composite filament. (5) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 2.5 times and a heat-setting temperature of 95°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0026] Embodiment 2:
[0027] (1) Under nitrogen protection, add 10g of PA66 powder that has passed through an 80-mesh sieve into 120g of N,N-dimethylformamide solution containing 30wt% formic acid, stir for 30min, then add 20g of potassium permanganate and 8g of sulfuric acid, stir for 20min, then add 2g of acrylic acid and 1.5g of methyl methacrylate, heat to 65°C, stir for 2h, then rinse with 10wt% sodium hydroxide aqueous solution 3 times, rinse with deionized water 3 times, and vacuum dry to obtain surface-modified PA; (2) Add 10 g of surface-modified PA to 120 g of N,N-dimethylformamide, stir for 30 min, then add 10 g of stearyl alcohol and 1.5 g of p-toluenesulfonic acid, heat to 80 °C, stir for 6 h, wash with anhydrous ethanol 3 times, wash with deionized water 3 times, and vacuum dry to obtain alkyl chain-modified PA; (3) drying the PTT slices, PA66 slices and alkyl chain modified PA respectively to obtain dried PTT slices with a water content of 26 ppm, dried PA slices with a water content of 26 ppm and dried alkyl chain modified PA with a water content of 27 ppm; (4) 48 g of dried PA chips and 12 g of dried alkyl chain modified PA were placed from the silo into twin screw extruder A, and 40 g of dried PTT chips were placed from the silo into twin screw extruder B. The temperatures of the four zones of twin screw extruder A were 265°C, 273°C, 276°C, and 280°C, respectively, and the temperatures of the four zones of twin screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt after being melted and homogenized in the twin screw extruder was passed through metering pump A with a frequency of 32 Hz, and the PTT melt was passed through metering pump B with a frequency of 20 Hz. The rate is 21Hz, and the melt enters the eccentric core-skin composite spinning assembly for distribution. The melt converges at the spinneret and is spun. The spinneret specification L / D is 0.9 / 0.4, and the spinning temperature is 270℃. Then, it is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 30℃, the side blowing speed is 0.2m / s, and the side blowing humidity is 75%. Finally, it is formed by oiling and winding. The speed of the first guide roller is 600m / min, the speed of the second guide roller is 620m / min, and the winding speed is 650m / min, so as to obtain PTT / PA eccentric core-sheath composite filaments. (5) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 3 times and a heat-setting temperature of 100°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0028] Embodiment 3:
[0029] (1) Under nitrogen protection, add 10 g of 80-mesh nylon chip powder to 120 g of N,N-dimethylformamide solution containing 30 wt% formic acid, stir for 30 min, then add 20 g of potassium permanganate and 8 g of sulfuric acid, stir for 20 min, then add 2 g of acrylic acid and 1.5 g of methyl methacrylate, heat to 65 ° C, stir for 2 h, then rinse with 10 wt% sodium hydroxide aqueous solution 3 times, rinse with deionized water 3 times, and vacuum dry to obtain surface-modified PA; (2) Add 10 g of surface-modified PA to 120 g of N,N-dimethylformamide, stir for 30 min, then add 10 g of stearyl alcohol and 1.2 g of p-toluenesulfonic acid, heat to 80 °C, stir for 6 h, wash with anhydrous ethanol 3 times, wash with deionized water 3 times, and vacuum dry to obtain alkyl chain-modified PA; (3) drying the PTT slices, PA slices and alkyl chain-modified PA respectively to obtain dried PTT slices with a water content of 25 ppm, dried PA slices with a water content of 25 ppm and dried alkyl chain-modified PA with a water content of 25 ppm; (4) 32 g of dried PA chips and 8 g of dried alkyl chain modified PA were placed from the silo into twin screw extruder A, and 60 g of dried PTT chips were placed from the silo into twin screw extruder B. The temperatures of the four zones of twin screw extruder A were 275°C, 288°C, 293°C, and 298°C, respectively, and the temperatures of the four zones of twin screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt after being melted and homogenized in the twin screw extruder passed through metering pump A with a frequency of 22 Hz, and the PTT melt passed through metering pump B with a frequency of 22 Hz. The frequency is 31Hz, and the melt is distributed in the eccentric core-skin composite spinning assembly. The melt is combined at the spinneret and spun. The spinneret specification L / D is 0.9 / 0.4, and the spinning temperature is 270°C. Then, the melt is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 30°C, the side blowing speed is 0.2m / s, and the side blowing humidity is 75%. Finally, the melt is formed by oiling and winding. The speed of the first guide roller is 600m / min, the speed of the second guide roller is 630m / min, and the winding speed is 650m / min, thereby obtaining PTT / PA eccentric core-sheath composite filaments. (5) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 3 times and a heat-setting temperature of 100°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0030] Embodiment 4:
[0031] (1) Under nitrogen protection, add 15 g of PA56 chips powder crushed through a 100 mesh sieve into 200 g of N,N-dimethylformamide solution containing 40 wt% formic acid, stir for 40 min, then add 30 g of potassium permanganate and 10 g of sulfuric acid, stir for 30 min, then add 3 g of acrylic acid and 2 g of methyl methacrylate, heat to 70 ° C, stir for 2.5 h, then rinse with 10 wt% sodium hydroxide aqueous solution 3 times, rinse with deionized water 3 times, and vacuum dry to obtain surface modified PA; (2) Add 15 g of surface-modified PA to 200 g of N,N-dimethylformamide, stir for 40 min, then add 15 g of stearyl alcohol and 2 g of p-toluenesulfonic acid, heat to 85 °C, stir for 7 h, wash with anhydrous ethanol 3 times, wash with deionized water 3 times, and vacuum dry to obtain alkyl chain-modified PA; (3) drying the PTT slices, PA56 slices and alkyl chain modified PA respectively to obtain dried PTT slices with a water content of 25 ppm, dried PA slices with a water content of 24 ppm and dried alkyl chain modified PA with a water content of 25 ppm; (4) 14 g of dried PA chips and 6 g of dried alkyl chain modified PA were placed from the silo into twin screw extruder A, and 80 g of dried PTT chips were placed from the silo into twin screw extruder B. The temperatures of the four zones of twin screw extruder A were 275°C, 288°C, 293°C, and 298°C, respectively, and the temperatures of the four zones of twin screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt after being melted and homogenized in the twin screw extruder was passed through metering pump A with a frequency of 12 Hz, and the PTT melt was passed through metering pump B with a frequency of 25 Hz. The frequency is 44Hz, and the melt is distributed in the eccentric core-skin composite spinning assembly. The melt is combined at the spinneret and spun. The spinneret specification L / D is 0.9 / 0.5, and the spinning temperature is 270°C. Then, the melt is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 35°C, the side blowing speed is 0.25m / s, and the side blowing humidity is 80%. Finally, the melt is formed by oiling and winding. The speed of the first guide roller is 650m / min, the speed of the second guide roller is 680m / min, and the winding speed is 720m / min, thereby obtaining PTT / PA eccentric core-sheath composite filaments. (5) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 3.5 times and a heat-setting temperature of 105°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0032] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the dry alkyl chain modified PA in step (4) is replaced by dry surface modified PA; The specific steps are as follows: (1) Under nitrogen protection, add 10g of PA66 powder that has passed through an 80-mesh sieve into 120g of N,N-dimethylformamide solution containing 30wt% formic acid, stir for 30min, then add 20g of potassium permanganate and 8g of sulfuric acid, stir for 20min, then add 2g of acrylic acid and 1.5g of methyl methacrylate, heat to 65°C, stir for 2h, then rinse with 10wt% sodium hydroxide aqueous solution 3 times, rinse with deionized water 3 times, and vacuum dry to obtain surface-modified PA; (2) Drying the PTT slices, PA66 slices and surface-modified PA respectively to obtain dried PTT slices with a water content of 26 ppm, dried PA slices with a water content of 26 ppm and surface-modified PA with a water content of 27 ppm; (3) 48 g of dried PA chips and 12 g of dried surface-modified PA were placed from the silo into twin-screw extruder A, and 40 g of dried PTT chips were placed from the silo into twin-screw extruder B. The temperatures of the four zones of twin-screw extruder A were 265°C, 273°C, 276°C, and 280°C, respectively, and the temperatures of the four zones of twin-screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt after being melted and homogenized in the twin-screw extruder passed through metering pump A with a frequency of 32 Hz, and the PTT melt passed through metering pump B with a frequency of 25 Hz. The frequency is 21Hz, and the melt is distributed in the eccentric core-skin composite spinning assembly. The melt is combined at the spinneret and spun. The spinneret specification L / D is 0.9 / 0.4, and the spinning temperature is 270°C. Then, the melt is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 30°C, the side blowing speed is 0.2m / s, and the side blowing humidity is 75%. Finally, the melt is formed by oiling and winding. The speed of the first guide roller is 600m / min, the speed of the second guide roller is 620m / min, and the winding speed is 650m / min, thereby obtaining PTT / PA eccentric core-sheath composite filaments. (4) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 3 times and a heat-setting temperature of 100°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0033] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the dried alkyl chain-modified PA in step (4) is replaced by PA slices; The specific steps are as follows: (1) Drying the PTT slices and the PA66 slices respectively to obtain dried PTT slices with a water content of 26 ppm and dried PA slices with a water content of 26 ppm; (2) 60 g of dried PA chips were placed from the silo into twin-screw extruder A, and 40 g of dried PTT chips were placed from the silo into twin-screw extruder B. The temperatures of the four zones of twin-screw extruder A were 265°C, 273°C, 276°C, and 280°C, respectively, and the temperatures of the four zones of twin-screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt melted and homogenized by the twin-screw extruder was passed through metering pump A with a frequency of 32 Hz, and the PTT melt was passed through metering pump B with a frequency of 21 Hz. Enter the eccentric core-skin composite spinning assembly for distribution, the melt converges at the spinneret, and the spinning is carried out. The spinneret specification L / D is 0.9 / 0.4, the spinning temperature is 270°C, and then it is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 30°C, the side blowing speed is 0.2m / s, and the side blowing humidity is 75%. Finally, it is formed by oiling and winding. The speed of the first guide roller for winding is 600m / min, the speed of the second guide roller is 620m / min, and the winding speed is 650m / min, so as to obtain PTT / PA eccentric core-sheath composite filaments; (3) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 3 times and a heat-setting temperature of 100°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0034] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the acrylic acid in step (1) is replaced by methyl methacrylate; The specific steps are as follows: (1) Under nitrogen protection, add 10 g of PA66 powder that has passed through an 80-mesh sieve into 120 g of N,N-dimethylformamide solution containing 30 wt% formic acid, stir for 30 min, then add 20 g of potassium permanganate and 8 g of sulfuric acid, stir for 20 min, then add 3.5 g of methyl methacrylate, heat to 65 °C, stir for 2 h, then rinse with 10 wt% sodium hydroxide aqueous solution 3 times, rinse with deionized water 3 times, and vacuum dry to obtain surface-modified PA; (2) Add 10 g of surface-modified PA to 120 g of N,N-dimethylformamide, stir for 30 min, then add 10 g of stearyl alcohol and 1.5 g of p-toluenesulfonic acid, heat to 80 °C, stir for 6 h, wash with anhydrous ethanol 3 times, wash with deionized water 3 times, and vacuum dry to obtain alkyl chain-modified PA; (3) drying the PTT slices, PA66 slices and alkyl chain modified PA respectively to obtain dried PTT slices with a water content of 26 ppm, dried PA slices with a water content of 26 ppm and dried alkyl chain modified PA with a water content of 27 ppm; (4) 48 g of dried PA chips and 12 g of dried alkyl chain modified PA were placed from the silo into twin screw extruder A, and 40 g of dried PTT chips were placed from the silo into twin screw extruder B. The temperatures of the four zones of twin screw extruder A were 265°C, 273°C, 276°C, and 280°C, respectively, and the temperatures of the four zones of twin screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt after being melted and homogenized in the twin screw extruder was passed through metering pump A with a frequency of 32 Hz, and the PTT melt was passed through metering pump B with a frequency of 20 Hz. The rate is 21Hz, and the melt enters the eccentric core-skin composite spinning assembly for distribution. The melt converges at the spinneret and is spun. The spinneret specification L / D is 0.9 / 0.4, and the spinning temperature is 270℃. Then, it is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 30℃, the side blowing speed is 0.2m / s, and the side blowing humidity is 75%. Finally, it is formed by oiling and winding. The speed of the first guide roller is 600m / min, the speed of the second guide roller is 620m / min, and the winding speed is 650m / min, so as to obtain PTT / PA eccentric core-sheath composite filaments. (5) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 3 times and a heat-setting temperature of 100°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0035] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that methyl methacrylate in step (1) is replaced by acrylic acid; The specific steps are as follows: (1) Under nitrogen protection, add 10 g of PA66 powder that has passed through an 80-mesh sieve into 120 g of N,N-dimethylformamide solution containing 30 wt% formic acid, stir for 30 min, then add 20 g of potassium permanganate and 8 g of sulfuric acid, stir for 20 min, then add 3.5 g of acrylic acid, heat to 65 °C, stir for 2 h, then rinse with 10 wt% sodium hydroxide aqueous solution 3 times, rinse with deionized water 3 times, and vacuum dry to obtain surface-modified PA; (2) Add 10 g of surface-modified PA to 120 g of N,N-dimethylformamide, stir for 30 min, then add 10 g of stearyl alcohol and 1.5 g of p-toluenesulfonic acid, heat to 80 °C, stir for 6 h, wash with anhydrous ethanol 3 times, wash with deionized water 3 times, and vacuum dry to obtain alkyl chain-modified PA; (3) drying the PTT slices, PA66 slices and alkyl chain modified PA respectively to obtain dried PTT slices with a water content of 26 ppm, dried PA slices with a water content of 26 ppm and dried alkyl chain modified PA with a water content of 27 ppm; (4) 48 g of dried PA chips and 12 g of dried alkyl chain modified PA were placed from the silo into twin screw extruder A, and 40 g of dried PTT chips were placed from the silo into twin screw extruder B. The temperatures of the four zones of twin screw extruder A were 265°C, 273°C, 276°C, and 280°C, respectively, and the temperatures of the four zones of twin screw extruder B were 235°C, 246°C, 249°C, and 255°C, respectively. The PA melt after being melted and homogenized in the twin screw extruder was passed through metering pump A with a frequency of 32 Hz, and the PTT melt was passed through metering pump B with a frequency of 20 Hz. The rate is 21Hz, and the melt enters the eccentric core-skin composite spinning assembly for distribution. The melt converges at the spinneret and is spun. The spinneret specification L / D is 0.9 / 0.4, and the spinning temperature is 270℃. Then, it is rapidly cooled and solidified into a filament bundle under side blowing. The side blowing temperature is 30℃, the side blowing speed is 0.2m / s, and the side blowing humidity is 75%. Finally, it is formed by oiling and winding. The speed of the first guide roller is 600m / min, the speed of the second guide roller is 620m / min, and the winding speed is 650m / min, so as to obtain PTT / PA eccentric core-sheath composite filaments. (5) The PTT / PA eccentric core-sheath composite filaments were stretched and heat-set at a stretching ratio of 3 times and a heat-setting temperature of 100°C to obtain PTT / PA eccentric core-sheath composite fibers.
[0036] Performance Testing: Tensile property test: According to GB / T14344-2008, the strength and elongation test was carried out, where the pre-tension was 0.05 cN / dtex, the clamping distance was 100 mm, and the stretching speed was 500 mm / min. The results are shown in Table 1.
[0037] Curl performance test: According to the standard GB / T 6506-2017, a load of 0.001 cN / dtex was applied to the composite fiber, and the composite fiber was placed in a 120 °C forced air oven for 10 min to make it curled. The composite fiber was taken out and balanced under standard atmospheric conditions for 30 min before the curl performance test.
[0038] Table 1 Tensile properties and elastic recovery test results
[0039] Data Analysis: From the data of Examples 1-4 in Table 2, it can be seen that the composite fiber prepared by the present invention has an obvious eccentric structure. When the breaking strength reaches 3.58N / dtex, it can still maintain a breaking elongation of 27.4%, and the curling shrinkage rate can reach more than 50%, which shows that the composite fiber not only has high strength and high toughness, but also has excellent elastic recovery performance. The design of the eccentric structure enables the fiber to effectively disperse stress when subjected to force and avoid brittle fracture. At the same time, the synergistic effect of the inner and outer layer materials enhances the ductility and fracture resistance of the fiber. In addition, the high curling shrinkage rate indicates that the fiber has good elasticity and recovery, and is suitable for use in industries, clothing and functional materials that require high elasticity and high strength.
[0040] From the data of Example 2 and Comparative Example 1 in Table 2, it can be seen that the alkyl chain on the alkyl chain-modified PA can significantly improve the curl shrinkage rate of the composite fiber. This is mainly because the introduction of the alkyl chain increases the flexibility and mobility of the PA molecular chain, making it easier for the fiber to form a stable eccentric structure during spinning and subsequent processing. In addition, the presence of the alkyl chain also enhances the interfacial compatibility between PA and PTT, so that the fiber has better elastic recovery performance during the curling process, thereby further improving the curl shrinkage rate. This characteristic makes the composite fiber excellent in elasticity and dimensional stability, and is suitable for application scenarios with high elasticity requirements.
[0041] From the data of Example 2 and Comparative Example 2 in Table 2, it can be seen that the alkyl chain-modified PA replaces part of the raw materials in the PA layer, which can significantly improve the breaking strength while slightly reducing the breaking elongation. This is mainly because the alkyl chain and methyl methacrylate on the surface of the alkyl chain-modified PA enhance the interfacial bonding between PA and PTT, improve the compatibility of the two materials, and reduce the stress concentration at the interface; on the other hand, it improves the flexibility and orientation of the PA molecular chain, so that it exhibits higher strength and stability in the fiber structure. This intermolecular entanglement and reinforcement effect enables the composite fiber to significantly improve the overall breaking strength while maintaining a certain toughness, making it suitable for application scenarios with high strength requirements.
[0042] From the data of Example 2 and Comparative Examples 3-4 in Table 2, it can be seen that the acrylic acid and methyl methacrylate on the surface of the surface-modified PA synergistically improve the breaking strength and curl shrinkage rate of the composite fiber. This is mainly because the acrylic acid provides a grafting site for the alkyl chain, and the grafted alkyl chain and methyl methacrylate jointly improve the binding force between PA and PTT and the interaction force between the molecular chains inside the fiber. The acrylic acid-grafted alkyl chain enhances the flexibility and orientation of PA through the entanglement and embedding between molecules. At the same time, methyl methacrylate further improves the interfacial compatibility between PA and PTT through its ester structure, reducing the interfacial stress concentration. In addition, methyl methacrylate may undergo an ester exchange reaction with PTT at high temperature to form partial chemical crosslinking, further enhancing the structural stability of the fiber. This synergistic effect not only significantly improves the breaking strength of the fiber, but also enhances the ability to form an eccentric structure, thereby improving the curl shrinkage rate, so that the fiber has excellent toughness and balanced elastic properties.
[0043] Dry heat shrinkage test: The composite fibers prepared in the embodiment and the comparative example were heat treated at 40°C, 80°C, 120°C and 160°C for 5 min, respectively, and static dry heat shrinkage test was carried out with a load of 0.01 cN / dtex. The results are shown in Table 2.
[0044] Table 2 Dry heat shrinkage test results
[0045] Data Analysis: From the data of Examples 1-4 in Table 2, it can be seen that the composite fiber prepared by the present invention has a low dry heat shrinkage rate. After being treated at 80°C for 10 minutes, the shrinkage rate is less than 2%, indicating that the composite fiber has extremely high dimensional stability in medium and low temperature environments, and almost no significant shrinkage occurs due to heat treatment. This property is very important for applications that need to maintain shape at lower temperatures (such as clothing and home textiles). Even at higher temperatures (160°C), the shrinkage rate of the fiber is still low, showing good thermal stability. This property is particularly critical for fibers that need to be used in high temperature environments (such as industrial fibers and heat-set fabrics).
[0046] It can be seen from the data of Example 2 and Comparative Example 1 in Table 2 that the alkyl chain on the alkyl chain-modified PA can effectively reduce the dry heat shrinkage of the composite fiber. This is mainly because the alkyl chain on the alkyl chain-modified PA can be entangled with the molecular chain of the inner layer PTT fiber during the spinning process, thereby limiting the automatic movement of the molecular chain of the PTT fiber at high temperature, and also limiting the automatic movement of the molecular chain of the outer layer PA at high temperature, thereby reducing the dry heat shrinkage of the composite fiber.
[0047] It can be seen from the data of Example 2 and Comparative Example 2 in Table 2 that the dry heat shrinkage of the composite fiber can be significantly reduced by replacing part of the raw materials in the PA layer with the alkyl chain-modified PA. This is mainly due to the synergistic effect of the alkyl chain and methyl acrylate on the alkyl chain-modified PA, which improves the bonding force between the PA layer and the inner layer PTT and optimizes the heat resistance of the PA layer.
[0048] It can be seen from the data of Example 2 and Comparative Example 3 in Table 2 that when PA is modified only with methyl methacrylate, the dry heat shrinkage of the composite fiber is relatively high. This is mainly because it is difficult to graft alkyl chains onto PA modified only with methyl methacrylate, making it difficult to exert the synergistic effect of alkyl chains and methyl methacrylate.
[0049] It can be seen from the data of Example 2 and Comparative Example 4 in Table 2 that the methyl methacrylate on the surface of the alkyl chain-modified PA can effectively reduce the dry heat shrinkage of the composite fiber, especially the dry heat shrinkage at high temperature. This is mainly because the methyl methacrylate on the surface of the alkyl chain-modified PA improves the compatibility between PA and PTT. As for the significant increase in the dry heat shrinkage at high temperature, it may be due to the ester exchange reaction between methyl methacrylate and PTT at high temperature. This chemical reaction further enhances the binding force between PA and PTT, forms a partial covalent bond connection, and limits the thermal motion of the molecular chain, so that the composite fiber exhibits a lower dry heat shrinkage at high temperature.
[0050] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A PTT / PA eccentric core-sheath composite fiber, characterized in that: It comprises a core layer and a sheath layer, wherein the raw material of the core layer comprises PTT slices, and the raw material of the sheath layer comprises PA slices and alkyl chain modified PA; The sheath layer accounts for 20%-80% of the total weight of the PTT / PA eccentric core-sheath composite fiber; The alkyl chain modified PA accounts for 10%-30% of the total weight of the sheath layer; The preparation method of the alkyl chain modified PA is as follows: Step S1: under nitrogen protection, PA slices are crushed through a 50-100 mesh sieve, added to an N,N-dimethylformamide solution containing 20wt%-40wt% formic acid, stirred for 20-40min, potassium permanganate and sulfuric acid are added, stirred for 10-30min, acrylic acid and methyl methacrylate are added, the temperature is raised to 60-70°C, stirred for 1.5-2.5h, washed, and vacuum dried to obtain surface-modified PA; Step S2: adding the surface modified PA to N,N-dimethylformamide, stirring for 20-40 min, then adding stearyl alcohol and p-toluenesulfonic acid, heating to 75-85° C., stirring for reaction for 5-7 h, washing, and vacuum drying to obtain alkyl chain modified PA; In the step S1, the weight ratio of PA slices, N,N-dimethylformamide solution of formic acid, potassium permanganate, sulfuric acid, acrylic acid and methyl methacrylate is 5-15:50-200:10-30:3-10:1-3:0.5-2; In the step S2, the weight ratio of the surface-modified PA, N,N-dimethylformamide, stearyl alcohol and p-toluenesulfonic acid is 5-15:50-200:5-15:0.5-2.
2. The PTT / PA eccentric core-sheath composite fiber according to claim 1, characterized in that: The PTT slices, PA slices and alkyl chain modified PA are dried before use, and the moisture content of the dried PTT slices, PA slices and alkyl chain modified PA is lower than 30 ppm.
3. The PTT / PA eccentric core-sheath composite fiber according to claim 1, characterized in that: The melting point of the PTT slice is 225-230° C., and the relative viscosity is 0.90-1.0; the melting point of the PA slice is 215-265° C., and the relative viscosity is 2.0-3.
2.
4. The PTT / PA eccentric core-sheath composite fiber according to claim 1, characterized in that: The PA slice is one of a PA6 slice, a PA66 slice, a PA56 slice, a PA11 slice or a PA12 slice.
5. The PTT / PA eccentric core-sheath composite fiber according to claim 1, characterized in that: The eccentricity of the PTT / PA eccentric core-sheath composite fiber is 0.1R-0.3R.
6. A method for preparing the PTT / PA eccentric core-sheath composite fiber according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Drying the PTT slices, PA slices and alkyl chain-modified PA respectively to obtain dry PTT slices, dry PA slices and dry alkyl chain-modified PA; (2) Put the dried PA slices and the dried alkyl chain modified PA from the silo into the twin screw extruder A, and put the dried PTT slices from the silo into the twin screw extruder B. The PA melt melted and homogenized by the twin screw extruder passes through the metering pump A, and the PTT melt passes through the metering pump B, and enters the eccentric core-skin composite spinning assembly for distribution. The melts converge at the spinneret, spin, and then quickly cool and solidify into a filament bundle under side blowing, and finally are formed by oiling and winding to obtain PTT / PA eccentric core-sheath composite filaments. (3) The PTT / PA eccentric core-sheath composite filaments are stretched and heat-set to obtain PTT / PA eccentric core-sheath composite fibers.
7. The method for preparing the PTT / PA eccentric core-sheath composite fiber according to claim 6, characterized in that: In the step (2), the temperatures of the four zones of the twin-screw extruder A are 225-275°C, 236-288°C, 240-293°C, and 242-298°C, respectively; the temperatures of the four zones of the twin-screw extruder B are 235-240°C, 246-255°C, 249-260°C, and 255-270°C, respectively; the frequency of the metering pump A is 12-47 Hz; and the frequency of the metering pump B is 11-44 Hz.
8. The method for preparing the PTT / PA eccentric core-sheath composite fiber according to claim 6, characterized in that: In the step (2), the specification L / D of the spinneret is 0.9 / 0.4-0.9 / 0.6; the spinning temperature is 270°C; the side blowing air temperature is 25-35°C, the wind speed is 0.15-0.25m / s, and the humidity is 70%-80%.
9. The method for preparing the PTT / PA eccentric core-sheath composite fiber according to claim 6, characterized in that: In the step (2), the speed of the first guide roller for winding is 550-650 m / min, the speed of the second guide roller is 570-680 m / min, and the winding speed is 600-720 m / min.
10. The method for preparing the PTT / PA eccentric core-sheath composite fiber according to claim 6, characterized in that: In the step (3), the drafting ratio is 2.5-3.5 times, and the heat setting temperature is 95-105°C.
Citation Information
Patent Citations
Skin-core type composite fiber bundle as well as preparation method and application thereof
CN114540982A
Skin-core polyamide-polyester composite fiber and preparation method thereof
CN115787131A
Composite synthetic textile fibres
GB896955A
Core-sheath type conjugate fiber and fiber structure including the same
JP2012193483A
Core / sheath type fiber, non-woven fabric including the fiber, laminate of the non-woven fabric, and article including the laminate
KR102036764B1
Cited By
Production process of low-density PTT / PA eccentric core-sheath composite elastic fiber
CN120485983A
Composite fiber and preparation method thereof
CN120945526A